Progress in microalgal mediated bioremediation systems for the removal of antibiotics and pharmaceuticals from wastewater - Chandel, Neha; Ahuja, Vishal; Gurav, Ranjit; Kumar, Vinod; Tyagi, Vinay Kumar; Pugazhendhi, Arivalagan; Kumar, Gopalakrishnan; Kumar, Deepak; Yang, Yung-Hun; Bhatia, Shashi Kant (Elsevier, 2022)
Worldwide demand for antibiotics and pharmaceutical products is continuously increasing for the control of disease and improvement of human health. Poor management and partial metabolism of these compounds result in the pollution of aquatic systems, leading to hazardous effects on flora, fauna, and ecosystems. In the past decade, the importance of microalgae in micropollutant removal has been widely reported. Microalgal systems are advantageous as their cultivation does not require additional nutrients: they can recover resources from wastewater and degrade antibiotics and pharmaceutical pollutants simultaneously. Bioadsorption, degradation, and accumulation are the main mechanisms involved in pollutant removal by microalgae. Integration of microalgae-mediated pollutant removal with other technologies, such as biodiesel, biochemical, and bioelectricity production, can make this technology more economical and efficient. This article summarizes the current scenario of antibiotic and pharmaceutical removal from wastewater using microalgae-mediated technologies.
Keywords: Antibiotics; Bioadsorption; Pharmaceuticals; Microalgae; Biodiesel; Bioelectricity